Thioredoxin interacting protein is a potential regulator of glucose and energy homeostasis in endogenous Cushing's syndrome. - Tove Lekva; Jens Bollerslev; Afaf Sahraoui; Hanne Scholz; Hege Bøyum; Johan Arild Evang; Kristin Godang; Pål Aukrust; Thor Ueland (PLoS ONE, 2013)
Recent studies have described bone as an endocrine organ regulating glucose metabolism, with insulin signaling regulating osteocalcin secretion and osteocalcin regulating β cell function. We have previously demonstrated increased bone expression of TXNIP in patients with endogenous Cushing's syndrome (CS), and we hypothesized that TXNIP could contribute to the dysregulated glucose metabolism in CS. We studied 33 CS patients and 29 matched controls, with bone biopsies from nine patients, before and after surgical treatment. In vitro, the effect of silencing TXNIP (siTXNIP) in osteoblasts, including its effect on human islet cells, was examined. Our major findings were: (i) The high mRNA levels of TXNIP in bone from CS patients were significantly associated with high levels of glucose and insulin, increased insulin resistance, and decreased insulin sensitivity in these patients. (ii) Silencing TXNIP in osteoblasts enhanced their OC response to insulin and glucose and down-regulated interleukin (IL)-8 levels in these cells. (iii) Conditional media from siTXNIP-treated osteoblasts promoted insulin content and anti-inflammatory responses in human islet cells. We recently demonstrated that the thioredoxin/TXNIP axis may mediate some detrimental effects of glucocorticoid excess on bone tissue in CS. Here we show that alterations in this axis also may affect glucose metabolism in these patients.